Correlation between the timing of diagnostic ureteroscopy for upper tract urothelial cancer and intravesical recurrence after radical nephroureterectomy - Luo, Zhenkai; Jiao, Binbin; Su, Caixia; Zhao, Hang; Yan, Yangxuanyu; Pan, Yijin; Ren, Jian; Zhang, Guan; Ding, Zhenshan (Frontiers in Oncology, 2023)
Objective: We aimed to evaluate the effect of the timing of diagnostic ureteroscopy (URS) on intravesical recurrence (IVR) following radical nephroureterectomy (RNU). Patients and Methods: The clinical data of 220 patients with upper tract urothelial carcinoma (UTUC) treated with RNU at our center from June 2010 to December 2020 were retrospectively analyzed. According to the timing of the URS, all patients were divided into three groups: the no URS group, the 1-session group (diagnostic URS immediately followed by RNU), and the 2-session group (RNU after diagnostic URS). Additionally, we analyzed IVR-free survival (IVRFS) using the Kaplan-Meier and Cox proportional regression methods. Results: The median follow-up period of these 220 patents was 41 (range: 2-143) months. Among them, 58 patients developed IVR following RNU. Kaplan-Meier curve displayed a significantly higher IVR rate in both treatment groups than in the no-URS group (p=0.025). In the subgroup of patients with renal pelvis cancer, the incidence of IVR was significantly higher in both treatment groups than in the group without URS (p=0.006). In univariate Cox proportional regression analysis, the two treatment groups were risk factors for IVR compared to the no-URS group [p=0.027, hazard ratio (HR): 1.93, 95% confidence interval (CI): 1.08-3.46]. The two-stage group (p=0.032, HR: 1.98, 95% CI: 1.08-3.65), positive urine pathology (p<0.001, HR: 8.12, 95% CI: 3.63-18.15), adjuvant chemotherapy (p<0.001, HR: 0.20, 95% CI: 0.10-0.38), and positive margin (p<0.0001, HR: 7.50, 95% CI: 2.44-23.08) were all identified as independent predictors in the multivariate. Conclusion: This study revealed that delayed RNU following diagnostic URS may increase the risk of postoperative IVR in patients with UTUC, preoperatively positive uropathology, and positive surgical margin were risk factors for IVR after RNU, while early postoperative chemotherapy may effectively prevent IVR. Delay of RUN after URS could increase the risk of IVR.